Comparison of 2-D and 3-D motion analysis in the calculation of lower-body joint angle - A pilot study - Parsonage, J.; Secomb, J. L.; Sheppard, J. M.; Ferrier, B. K.; Dowse, R. A.; Nimphius, S. (Journal of Australian Strength and Conditioning, 2017)
Whilst three-dimensional (3-D) motion analysis is recognised as the `gold standard` for measuring joint kinematics, its implementation requires financial investment and trained staff. In comparison, the validity of two-dimensional (2-D) analysis for measuring joint angles during a countermovement jump (CMJ) is yet to be assessed. The current study aimed to assess the concurrent validity of 2-D motion analysis compared to 3-D motion analysis, in measuring sagittal plane knee flexion and extension during a CMJ.